PENGEMBANGAN MOUL BERBASIS PENEMUAN TERBIMBING UNTUK MATERI SUKU BANYAK PADA PEMBELAJARAN MATEMATIKA SISWA KELAS XI IPA SMA TAMAN SISWA PADANG - Roski, Adrida Muttiana (STKIP PGRI Sumbar, 2014)
This research was background by the use of teaching materials that do notcontain all the material students systematically with basic competence. Requiredinstructional materials that guide students to learn independently in the form ofmodules. The module is a module which was developed based guided discovery.This study aims to develop a guided discovery-based modules for material TribeMany valid and practical in high school Tamansiswa Padang. This type ofresearch is the development of research, this development using 4-D modelsconsisting of four stages: define, design, develop, and disseminate. In this study,the research phase is limited to the extent that stage develop the validity andpracticalities. The research instrument is (1) sheet validation, (2) questionnairepracticalities and (3) guidelines for the interview. 3,2 Validation module has avalidity of a valid category. questionnaire results practicality with pratikalitas85,63% teachers have very practical category. The results of the questionnairepracticality with 94,08% students have pratikalitas very practical category. It canbe concluded that the guided discovery-based modules for learning the materialpolynomials in high school math class XI IPA Tamansiswa Padang that has beengenerated can be declared valid and practical.